Fenomenologi Konten Kreator Dalam Mengedukasi Masyarakat Melalui Media Sosial Tiktok - Zhazaretta, Ananda; Djuhardi, Lidia (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
TikTok social media has become an important platform for content creators to disseminate variousinformation, including education for the community. Related to the dissemination of educationalinformation, this study aims to find out the experiences and motivations of content creators in presentingeducational content on Tik Tok media, as well as how they interpret it. The research approach is qualitativewith a phenomenological study, to explore the experiences, motivations and meanings of content creators ineducating the public on TikTok. Through the analysis of qualitative data from in-depth interviews andobservations with several education-focused content creators, this study identifies essential patterns in theexperiences and the ways content creators make meaning of them. The informants are purposively selectedcontent creators who have experience in their field, especially in educational content. The results of thestudy reveal that some of the informants' experiences in creating and presenting their content are veryinteresting because they involve the emotional content of the creators and the audience. This is alsosupported by their motivation in providing educational information. Meanwhile, the meaning of educationthrough TikTok media for content creators is that TikTok is seen as an effective tool for conveyinginformation in a creative way and is able to attract the attention of a wider audience. The implications ofthese findings explain a deeper understanding of the role of TikTok content creators in educating, where TikTok is not only considered a medium of entertainment, but also beneficial for society, especially ineducating the public.